2011
DOI: 10.5194/bg-8-289-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal monsoons on net community production and CO<sub>2</sub> in subtropical Hong Kong coastal waters

Abstract: Abstract. Data from seven cruises in three different environments including the Pearl River estuary, sewage discharge outfall, and eastern coastal/shelf waters were used to examine the seasonal variations in net community production (NCP) and the biologically active gases O 2 and CO 2 . In the winter dry season, when monsoon-induced downwelling was dominant, NCP was negative (−84 ± 50 mmol C m −2 d −1 ) in all three regions. The negative NCP corresponded to O 2 influxes of 100 ± 50 mmol O 2 m −2 d −1 and CO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 55 publications
1
21
1
Order By: Relevance
“…32 The harbor is impacted by other forms of human activities, e.g., there were 190 859 vessel arrivals with 26 million passengers for the marine ferry terminals in 2012. It is also home to the third largest container port in the world, with a total throughput of 23.1 million 20-Ft units in 2012.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32 The harbor is impacted by other forms of human activities, e.g., there were 190 859 vessel arrivals with 26 million passengers for the marine ferry terminals in 2012. It is also home to the third largest container port in the world, with a total throughput of 23.1 million 20-Ft units in 2012.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Gold Coast residential canal system had pCO 2 values and CO 2 evasion rates within the broad range observed in other estuaries (Chen et al, 2013). For example, it was found that the Piauí River (Brazil) had evasion rates of 35 mmol C m −2 d −1 (Raymond et al, 2000) while studies in the Randers Fjord, Denmark recorded ranges from − 5 mmol C m −2 d −1 in April and 53 mmol C m −2 d −1 in August (Gazeau et al, 2005) 24 mmol C m −2 d −1 (Yuan et al, 2011). Most studied estuaries are river dominated and influenced by human settlement (Cai, 2011).…”
Section: Canals As a Source Of Co 2 To The Atmospherementioning
confidence: 93%
“…The Yellow Sea is a marginal sea of the Pacific Ocean and located in the northern part of the East China Sea. The collection site experiences minimal freshwater influence from nearby rivers and thus have a typical coastal oceanic conditions with mean summer water temperature of 23°C, salinity of 30 to 31 ‰ and pH 8.1 to 8.2 [30], [31]. The collected broodstocks were transported in emersed condition to Hong Kong (22° 15'N, 114° 10'E) by air via Guangzhou (China).…”
Section: Methodsmentioning
confidence: 99%